2021
DOI: 10.21037/tau-21-250
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of prostate cancer diagnosis in biopsy-naive patients using combined magnetic resonance imaging and transrectal ultrasound fusion-targeted prostate biopsy

Abstract: Background: This study aimed to estimate whether multiparametric magnetic resonance imaging (mpMRI)-transrectal ultrasound (TRUS) fusion biopsy (FUS-TB) increases the detection rates of clinically significant prostate cancer (csPCa) compared with TRUS-guided systematic biopsy (TRUS-GB).Methods: This retrospective study focused on patients who underwent mpMRI before prostate biopsy (PB) with Prostate Imaging Reporting and Data System version 2 (PI-RADS v2) scores ≥3 and prostate-specific antigen (PSA) level bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Furthermore, there was no significant difference in the GG concordance rate between TBx and SBx in surgical specimens (38.2% vs. 39.5%) in this study. Thus, this may not reflect the pathophysiology of PCa status, even though TBx may detect malignant neoplasms of the prostate with high sensitivity [ 9 , 10 ]. To date, evidence regarding their predictors remains scarce, even though many studies have evaluated the discrepancies in GG between NB and RP specimens [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there was no significant difference in the GG concordance rate between TBx and SBx in surgical specimens (38.2% vs. 39.5%) in this study. Thus, this may not reflect the pathophysiology of PCa status, even though TBx may detect malignant neoplasms of the prostate with high sensitivity [ 9 , 10 ]. To date, evidence regarding their predictors remains scarce, even though many studies have evaluated the discrepancies in GG between NB and RP specimens [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…GG was accepted by the World Health Organization for the 2016 edition of Pathology and Genetics, and the GG 1–5 terms were proposed as the new grading system by the 2014 International Society of Urological Pathology (ISUP) consensus conference [ 8 ]. Additionally, according to several guidelines, the combination of targeted biopsy (TBx) of suspicious lesions on multiparametric magnetic resonance imaging (MRI) and transrectal ultrasound-guided (TRUS) systematic biopsy (SBx) for the prostate has produced more favorable PCa detection rates than was previously possible [ 2 , 3 , 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated the advantage of FBx over SBx in the detection of csPCa [11,[26][27][28][29][30][31]. In 2018, Kasivisvanathan et al reported the randomized controlled trial of 500 men with PCa suspicion, randomly assigned for FBx or SBx-the PRECISION trial [11].…”
Section: Multiparametric Mri In the Prostate Cancer Diagnosticsmentioning
confidence: 99%
“…Several recent studies have demonstrated the advantage of FBx over SBx in the detection of csPCa [11,[26][27][28][29][30][31]. In 2018, Kasivisvsanathan et al reported the randomized controlled trial of 500 men with PCa suspicion, randomly assigned for FBx or SBx -the PRE-CISION trial [11].…”
Section: Multiparametric Mri In the Prostate Cancer Diagnosticsmentioning
confidence: 99%